2017
DOI: 10.1038/s41598-017-11999-z
|View full text |Cite
|
Sign up to set email alerts
|

Coprophagous features in carnivorous Nepenthes plants: a task for ureases

Abstract: Most terrestrial carnivorous plants are specialized on insect prey digestion to obtain additional nutrients. Few species of the genus Nepenthes developed mutualistic relationships with mammals for nitrogen supplementation. Whether dietary changes require certain enzymatic composition to utilize new sources of nutrients has rarely been tested. Here, we investigated the role of urease for Nepenthes hemsleyana that gains nitrogen from the bat Kerivoula hardwickii while it roosts inside the pitchers. We hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 54 publications
0
6
0
1
Order By: Relevance
“…Interestingly, the final enzymatic step to release ammonia from ureides is catalyzed by a urease. Its presence and activity were recently demonstrated for Nepenthes and other carnivorous plants [41]. Whether or not this scenario mirrors the nitrogen translocation and distribution that occurs in Nepenthes remains to be elucidated.…”
Section: Metabolite Differences In Nepenthes Tissues: Leaf Blade Vs mentioning
confidence: 85%
See 1 more Smart Citation
“…Interestingly, the final enzymatic step to release ammonia from ureides is catalyzed by a urease. Its presence and activity were recently demonstrated for Nepenthes and other carnivorous plants [41]. Whether or not this scenario mirrors the nitrogen translocation and distribution that occurs in Nepenthes remains to be elucidated.…”
Section: Metabolite Differences In Nepenthes Tissues: Leaf Blade Vs mentioning
confidence: 85%
“…Following this thread, it may also explain why no effect of feeding was found in the leaf blades. Experiments with N. hemsleyana , a coprophagous Nepenthes species that does not catch prey any more but feeds on bat feces [ 44 ], showed that upon 15 N-enriched urea application into pitchers, after only four days, 15 N was significantly detectable in protein fractions of leaf blades [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests significant role of common hydrolytic enzymes, especially phosphatases, proteases, and chitinases, in prey digestion of various carnivorous plants regardless of different families or trapping mechanisms. Recently, Yilamujiang et al (2017) reported the presence of a novel digestive enzyme urease in N. hemsleyana which has developed a symbiosis relationship with bat.…”
Section: Digestive Enzyme Discovery Identification and Characterisatmentioning
confidence: 99%
“… * Present. References: [1] Fukushima et al, 2017 ; [2] Schulze et al, 2012 ; [3] Pavlovic, Jaksova & Novak, 2017 ; [4] Pavlovic et al, 2013 ; [5] Butts, Bierma & Martin, 2016 ; [6] Unhelkar et al, 2017 ; [7] Matušíková et al, 2005 ; [8] Michalko et al, 2013 ; [9] Jopcik et al, 2017 ; [10] Morohoshi et al, 2011 ; [11] Amagase, 1972 ; [12] Sirova, Adamec & Vrba, 2003 ; [13] Płachno et al, 2006 ; [14] Luciano & Newell, 2017 ; [15] Porembski & Barthlott, 2006 ; [16] Adlassnig, Peroutka & Lendl, 2010 ; [17] Jaffe et al, 1992 ; [18] Mithöfer, 2011 ; [19] Srivastava et al, 2011 ; [20] Hatano & Hamada, 2008 ; [21] Rottloff et al, 2016 ; [22] Takeuchi et al, 2011 ; [23] Lee et al, 2016 ; [24] Schrader et al, 2017 ; [25] Kadek et al, 2014a ; Kadek et al, 2014b ; [26] Higashi et al, 1993 ; [27] Buch et al, 2015 ; [28] Stephenson & Hogan, 2006 ; [29] Athauda et al, 2004 ; [30] Yilamujiang et al, 2017 ; [31] Eilenberg et al, 2006 ; [32] Renner & Specht, 2013 ; [33] Tokes, Woon & Chambers, 1974 ; [34] Thornhill, Harper & Hallam, 2008 . …”
Section: Digestive Enzyme Discovery Identification and Characterisatmentioning
confidence: 99%
“…Recently, Yilamujiang et al, (2017) reported the presence of a novel digestive enzyme urease in N. hemsleyana which has developed a symbiosis relationship with bat.…”
Section: Digestive Enzyme Discovery Identification and Characterisationmentioning
confidence: 99%